"Not from home": Cancer screening avoidance and the safety of distance in Eswatini. (January 2021) - Malambo, Nomthandazo
Abstract: This paper shows how travel and distance make cervical cancer screening safer for women in Eswatini. It is based on three months of original ethnographic research conducted in a semi-urban town in Eswatini from September to December 2014, involving daily participant observation and semi-structured, in-depth interviews with 20 women and 7 health workers. Results of the research show how women use travel to create safer clinical spaces and encounters in the context of cancer screening. Specifically, the research found that in the cervical cancer screening clinic, women's bodies are negatively judged and talked about. This creates fear – of judgment, verbal violence and gossip – all of which are intensified in hospitals and with nurses who are close to home. It is a fearful, laborious and difficult clinical encounter which causes a medical migration, where women seek screening in distant hospitals and with nurses who are "not from home." Distance provides anonymity and minimizes pathways of gossip, thus mitigating fear and making cervical cancer screening safer for women. The social rationale around distance shows how travel can create or recreate clinical spaces and experiences of care in the context of local medical migration. It also upsets culturalist assumptions about women's avoidance of cervical screening. Improving cancer screening programs in Eswatini calls for an approach sensitive to the clinical and social realities that create fear and constrain women's choices. Highlights: Women fear judgment and gossip in the cervical cancer screening clinic. They choose to attend screening with nurses who are "not from home." Distance and travel help make cancer screening safer for women. Understanding the local contexts of fear helps improve cancer screening programs.